Role of Power of Attorney in Marriage Nullity Proceedings: Canons 1478; 1479 and 1508 - Dungan, Patricia M. (CLSA advisory opinions, 2001-2005, 2001)
Should a marriage tribunal allow a respondent's civil power of attorney agent to act on his or her behalf during marriage annulment proceedings? Should the tribunal appoint a curator in such a situation?